Bringing down the house: From spectacular explosions to piece-by-piece removal, the way we demolish buildings reflects the shameful loss of social ideals. - Blake, Eddie (Architectural Review, 2019)
The article focuses on the value and meaning of building demolition and its impact on the society. It offers overview of the different processes involved in demolition, which became a controversial subject and public spectacle. It also mentions the complexities involved in the process since it requires structural analysis by investigating the site condition and understanding the impact of the adjacent property.